2012
DOI: 10.1007/s00204-012-0863-x
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine effect of EGFR ligands on the pro-inflammatory response induced by PM2.5 exposure in human bronchial epithelial cells

Abstract: Human exposure to PM(2.5) (particulate matter with an aerodynamic diameter below 2.5 μm) is known to be responsible for airway inflammation and may also induce airway remodelling. In respiratory epithelial cells exposed to PM(2.5), releases of pro-inflammatory cytokines such as granulocyte macrophage-colony stimulating factor (GM-CSF) and growth factor ligands of the epidermal growth factor receptor (EGFR) are increased. The present study aimed at determining the involvement of EGFR ligands by autocrine effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This induction was previously associated with organic compounds of particles and their ability to induce reactive oxygen species (ROS) overproduction [36,37], an effect also evaluated in this study.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…This induction was previously associated with organic compounds of particles and their ability to induce reactive oxygen species (ROS) overproduction [36,37], an effect also evaluated in this study.…”
Section: Resultsmentioning
confidence: 75%
“…Previous studies at the laboratory demonstrated that PM 2.5 of different sites induced AREG mRNA expression in 16HBE cells and primary human bronchial epithelial cells NHBE [16,34] and was implicated in the persistence of GM-CSF pro-inflammatory response [35,36]. Consequently, its overexpression was suspected of participating in airway epithelium remodeling.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is still some controversy regarding the role of the NLPR3 inflammasome upon pollutant exposure . Alternatively, ambient PM can also enhance the expression and activation of different membrane‐associated receptors, such as the epidermal growth factor receptor (EGFR) . Dimerization of the EGFR will stimulate tyrosine kinase activity that can elicit PI3K/AKT signalling and mitogen‐activated protein kinases (MAPK) (ie ERK, JNK and p38), both involved in the activation of the transcription factor NF‐κB .…”
Section: Air Pollution and The Airway Epitheliummentioning
confidence: 99%
“…58,59 Alternatively, ambient PM can also enhance the expression and activation of different membrane-associated receptors, such as the epidermal growth factor receptor (EGFR). [60][61][62][63][64][65] Dimerization of the EGFR will stimulate tyrosine kinase activity that can elicit PI3K/AKT signalling and mitogenactivated protein kinases (MAPK) (ie ERK, JNK and p38), both involved in the activation of the transcription factor NF-jB. 30,63,[66][67][68][69] Importantly, after internalization or PRR activation, exposure to ambient PM/DEPs will activate oxidative stress responses in the airway epithelial cells.…”
Section: Air Pollution and The Airway Epitheliummentioning
confidence: 99%
“…Moreover we demonstrated that EGFR ligands have an autocrine effect on the epithelium leading to a sustained pro-inflammatory response and mucus production [6,7]. The increased EGFR ligands expression induced by PM exposure could also act as a potent mitogenic factor for fibroblasts as some experimental studies have implicated EGFR signaling in pulmonary fibrosis [8].…”
Section: Introductionmentioning
confidence: 72%